2008
DOI: 10.1021/ma801598y
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Coil/Liquid-Crystalline Diblock Copolymers in a Liquid Crystal Solvent

Abstract: The SANS and rheology experiments reported in the main text were also performed on a set of coil/SGLCP diblocks having mesogenic side-groups attached "side-on", with the mesogen's long axis parallel to the polymer backbone ( Figure S1). Side-on and end-on polymers were synthesized from the same set of four PS-PB diblocks and one PB homopolymer using methods described in Reference 36. Side-on polymer properties are summarized in Table S2.All experimental methods for side-on and end-on polymers were identical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…A similar trend has been observed for AB-diblock copolymers comprising a PS-block and a functionalized side group liquid crystalline segment. In mixtures with 5CB the microphase separation temperature was influenced by the length of the PS-segments and could be adjusted above or below the T ni [16].…”
Section: Rheologymentioning
confidence: 99%
See 2 more Smart Citations
“…A similar trend has been observed for AB-diblock copolymers comprising a PS-block and a functionalized side group liquid crystalline segment. In mixtures with 5CB the microphase separation temperature was influenced by the length of the PS-segments and could be adjusted above or below the T ni [16].…”
Section: Rheologymentioning
confidence: 99%
“…Later on, Finkelmann et al have shown that the block copolymer segment containing the mesogenic moieties feature a selective solubility in the low molecular weight liquid crystals, whereas the isotropic block is not soluble in the LC solvent [13]. As a result, the flexible segments of an AB-diblock copolymer associate and form a micelle core that is surrounded by a corona of soluble liquid crystalline blocks [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported coilcoil block copolymers, 1-3 polymeric surfactants, [4][5][6] wormlike micelles, 7,8 and rod-coil block copolymers with rigid blocks. [9][10][11][12][13] The stiff or rigid segments as one of the blocks results in liquid crystalline ordering. [14][15][16][17][18] Diblock copolymers with side-chain liquid crystalline polymers and lyotropic chromonic liquid crystals 19,20 with a plate-like or disk-like central core have also attracted more attention in the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…From a practical viewpoint, such nanostructures also received considerable attention for fabrication of even smaller feature than those obtained by the photolithography process 7–9. Such nanostructures have potential applications in high‐density data storage media,10, 11 ultrafine filters or membranes,12 as templates for metal nanowires,13, 14 and so forth 15…”
Section: Introductionmentioning
confidence: 99%